Some Basic Properties of Almost-Prime Left Ideals in Г-Semirings - Yiarayong, Pairote (Agriculture and Natural Resources, 2015)
The purpose of this paper was to introduce the notion of almost-prime left ideals in Г-semirings by studying prime and weakly almost-prime left ideals in Г-semirings. Some characterizations of almost-prime and weakly almost-prime left ideals were obtained. Moreover, the relationships between almost-prime and weakly almost-prime left ideals in Г –semirings were investigated.